Scattering of radio frequency waves by cylindrical filaments with general orientation relative to the magnetic field. (December 2018) - Valvis, S. I.; Ram, A. K.; Hizanidis, K.; Papagiannis, P.; Papadopoulos, A.; Zisis, A.; Tigelis, I. G.; Glytsis, E.
Abstract : Radio frequency (RF) waves are routinely used in tokamak fusion plasmas for plasma heating, current control, as well as in diagnostics. These waves are excited by antenna structures placed near the tokamak's wall and they have to propagate through a turbulent layer known as the scrape-off layer, before reaching the core plasma (which is their target). This layer exhibits coherent density fluctuations in the form of filaments and blobs. The scattering processes of RF plane waves by a single filament is studied with the assumption that the filament has a cylindrical shape and infinite length. Furthermore, besides the major toroidal component of the externally imposed magnetic field, there is also a small poloidal magnetic field component. Considering also that the cylindrical filament's axis is not necessarily aligned with the toroidal direction, the total magnetic field is in general neither aligned with the axis of the cylinder nor with the toroidal direction. The investigation concerns the case of electron cyclotron (EC) waves (of frequency $f_{0}=170~\text{GHz}$ ) for tokamak applications. The study covers a variety of density contrasts between the filament and the ambient plasma, different magnetic field inclinations with respect to the cylinder axis (for the same magnitude of magnetic induction $B=4.5T$ ) and a wide range of filament radii.